2023
DOI: 10.1038/s41591-023-02633-9
|View full text |Cite
|
Sign up to set email alerts
|

A digital health algorithm to guide antibiotic prescription in pediatric outpatient care: a cluster randomized controlled trial

Rainer Tan,
Godfrey Kavishe,
Lameck B. Luwanda
et al.

Abstract: Excessive antibiotic use and antimicrobial resistance are major global public health threats. We developed ePOCT+, a digital clinical decision support algorithm in combination with C-reactive protein test, hemoglobin test, pulse oximeter and mentorship, to guide health-care providers in managing acutely sick children under 15 years old. To evaluate the impact of ePOCT+ compared to usual care, we conducted a cluster randomized controlled trial in Tanzanian primary care facilities. Over 11 months, 23,593 consult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The study also revealed a two-fold reduction in antibiotic prescriptions (adjusted relative risk 0.5, 95% CI 0.4 to 0.7), and 50% improvement in the appropriate use of antibiotics in health facilities using ePOCT+ (adjusted relative risk 1.5 (95% CI 1.2 to 1.8), critical findings given the global concern for bacterial antimicrobial resistance [47]. Similar reductions were found in the parent trial using the intention-to-treat results over the full 11 month trial period (adjusted relative risk 0.6 (95% CI 0.5 to 0.6),[24] and in the same 5-week period as the present trial (adjusted relative risk 0.4, 95% CI 0.2 to 0.7). However, the documented antibiotic prescription as observed by external clinical researchers was slightly higher than what was documented by the health providers in ePOCT+ (intervention health facilities) and the eCRF (control health facilities), suggesting that some health providers may under report antibiotic prescription in ePOCT+ and the eCRF.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The study also revealed a two-fold reduction in antibiotic prescriptions (adjusted relative risk 0.5, 95% CI 0.4 to 0.7), and 50% improvement in the appropriate use of antibiotics in health facilities using ePOCT+ (adjusted relative risk 1.5 (95% CI 1.2 to 1.8), critical findings given the global concern for bacterial antimicrobial resistance [47]. Similar reductions were found in the parent trial using the intention-to-treat results over the full 11 month trial period (adjusted relative risk 0.6 (95% CI 0.5 to 0.6),[24] and in the same 5-week period as the present trial (adjusted relative risk 0.4, 95% CI 0.2 to 0.7). However, the documented antibiotic prescription as observed by external clinical researchers was slightly higher than what was documented by the health providers in ePOCT+ (intervention health facilities) and the eCRF (control health facilities), suggesting that some health providers may under report antibiotic prescription in ePOCT+ and the eCRF.…”
Section: Discussionmentioning
confidence: 89%
“…Initially, antibiotic prescription was considered a co-primary outcome alongside the current primary outcome (proportion of 14 major IMCI symptoms and signs), but was later reclassified as a secondary outcome. We made this change to focus the analysis on quality of care, given that antibiotic prescription was already the primary outcome of the large longitudinal cluster randomized trial [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation